Tjalma syndrome: A rare manifestation of systemic lupus erythematosus - Ashwaq Alhmoudi; Ahlam Almarzooqi; Maryam Alahmad; Amna Al Muhairi; Sehriban Diab; Raven Haan; Khalid Elsayed (Indian Journal of Rheumatology)
Tjalma syndrome, also known as pseudo-pseudo Meigs' syndrome, is a rare manifestation of conditions in patients with systemic lupus erythematosus (SLE). The syndrome is characterized by the presence of ascites, pleural effusion, and an elevated cancer antigen-125 (CA-125) level. We present the case of a 27-year-old female patient admitted in 2021 without any comorbidities, who presented with unintentional weight loss, gastrointestinal upset, and ascites. Further evaluation showed elevated CA-125 levels and pleural effusions, with no atypical cells. The patient was initially treated with antiemetics, intravenous fluids, antibiotics, and total parental nutrition with no improvement in her symptoms or laboratory parameters. The results of an autoimmune workup met the criteria for the classification of SLE. After extensive investigation, she was diagnosed with Tjalma syndrome. She was subsequently treated with corticosteroids and hydroxychloroquine, resulting in the rapid resolution of the patient's nausea and emesis, and discharge from the hospital. Her ascites resolved over 4 weeks. Prednisolone was tapered down and azathioprine was added as a steroid-sparing agent. The patient eventually had complete remission of her symptoms, as well as remarkable improvements in her laboratory results. However, 8 months after her initial diagnosis, the patient showed signs of increasing SLE activity with lupus nephritis, anemia, and leukopenia, despite being compliant with her treatment regimen. The patient was initiated on oral prednisolone (1 mg/kg) and azathioprine was replaced with mycophenolate mofetil, which resulted in significant improvement of clinical and laboratory parameters within 3 weeks. Cases of Tjalma syndrome, and specifically, this presentation, are rarely reported in the literature. We present this condition to raise awareness about both the presenting symptoms and therapeutic options for Tjalma syndrome.